Improving the Ability to Write Fantasy Stories Using Audio Visual Learning Media - Chostantinus, Windy; Somelok, Grace (Mirlam: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research aims to describe the improvement in the ability to write fantasy stories using audio-visual media for students in class VII-6 at SMP Negeri 19 Ambon. The method used is the Classroom Action Research (PTK) method with data collection techniques, namely interviews, questionnaires, tests and documentation. The research results obtained show that learning to write fantasy stories using audio-visual media can create a learning atmosphere that allows students to be more active in class and can increase students' interest in learning which influences learning outcomes. The results of the assessment of writing fantasy stories using audio-visual media showed an increase in the number of students achieving the KKM. The average score obtained by class VII-6 students at SMP Negeri 19 Ambon in cycle I was 64.65 with the percentage of students who reached the KKM being 11 students. Meanwhile, the average score obtained by class VII-6 students at SMP Negeri 19 Ambon in cycle II was 75.57 with the number of students achieving the KKM as many as 25 students. This data shows a comparison that indicates an increase in the ability to write fantasy stories in class VII-6 students at SMP Negeri 19 Ambon.